The chromatin remodeling protein BRG1 modulates BRCA1 response to UV irradiation by regulating ATR/ATM activation - Zhang, Ling; Chen, Hua; Gong, Ming; Gong, Feng (Frontiers in Oncology, 2013)
The SWI/SNF chromatin remodeling complex plays a role in the repair of UV-induced DNA damage. It was proposed that chromatin remodeling activities are utilized to increase the accessibility of NER machinery and checkpoint factors to the damaged DNA. It was shown recently that BRCA1 contributes to UV damage response by promoting photoproduct excision, triggering post-UV checkpoint activation and post replicative repair. In this study, we show that BRCA1 rapidly binds to UV damage sites when cells are undergoing DNA synthesis. In contrast, two phosphorylated forms of BRCA1 do not accumulate at sites of UV damage. Depletion of BRG1, a core subunit of the human SWI/SNF-BAF complex, impairs the recruitment of BRCA1 to the damage sites and attenuates DNA damage induced BRCA1 phosphorylation. At UV lesions-stalled replication forks, BRG1 promotes RPA phosphorylation in response to UV irradiation, since UV-induced phosphorylation of chromatin bound RPA drops significantly when BRG1 is depleted in human cells. Importantly, activation of the ATM/ATR kinases is attenuated when BRG1 is depleted. We propose that BRG1 modulates BRCA1 response to UV irradiation by regulating ATM/ATR activation.